Pengaruh Karakter Siswa dan Motivasi Belajar terhadap Kompetensi Belajar Akidah Akhlak Siswa Madrasah Aliyah Negeri Kabupaten Kuningan - Afriyanti, Diah Nur; Saepudin; Suryamih, Iim; Hasbian, Yanti (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The background of this research is that there is still no effective competence to learn morality because competence is knowledge, skills, and abilities that have become part of one's self. The objective of this research is to know the positive influence of student character on the competence of learning in academia, to understand the positive impact of learning motivation on competence, and to know the positive impact of the character of students on the motivation of learning. This research method uses quantitative research with the partial least squares (PLS) approach and structural equation modeling (SEM). The sample is 150 students and using simple random sampling tecnict. The results of the study were positive and statistically significant for the direct influence of student character on the learning competence, Learning motivation has a direct positive and statistically significant influence on the learning competence, positive and statistically significant for the direct influence of student character on learning motivation. The result of the calculation of the path coefficient (Path Coefisien) was the equation KB = 0.898 KS + 0.389 MB, which means that the competence of learning in academia of 56.7% can be explained by the character of the student and 38.9% by the learning motivation variable with a constellation value of 0.898. The results of the data analysis show a value = R-square adjusted of 0.931, which means that 93.1% of the variation of the endogenous variable of learning competence can be explained by the exogenic variables of student character and learning motivation, when the remaining 6.9% is explained by variations of change not included in this model.